Trends in Helicobacter pylori Infection - Maria Roesler, Bruna (IntechOpen, 2014)
Helicobacter pylori is a universally distributed bacterium which affects more than half of the world population. The infection is associated with the development of various diseases of the upper gastrointestinal tract, besides extradigestive diseases. This book is a comprehensive overview of contributors on H. pylori infection in several areas. Its chapters were divided into sections concerning general aspects of H. pylori infection, immunopathology and genetic diversity, questions regarding possible routes of bacterium transmission, the importance of the strains characteristics in the development of gastric cancer and the possibilities of prevention, H. pylori infection in children, the possible association between its infection and extradigestive diseases, and the principal therapeutic regimens of bacterium eradication, considering the antimicrobial resistance.